The Correlation of Vibration Signal Features in Grinding of Advanced Ceramics - Conceicao Junior, P. O. [UNESP]; Marchi, M. [UNESP]; Aguiar, P. R. [UNESP]; Bianchi, E. C. [UNESP]; Franca, T. V. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2016)
Monitoring the grinding of ceramics using the vibration signal has been presented as an alternative for the diagnosis of the workpiece surface. This paper has the objective of studying the vibration signal through spectral analysis in order to monitor the grinding process, and looking for the best parameters that could be related to the surface integrity in the finished workpieces of ceramics. Thus, grinding tests were carried out on alumina ceramic specimens in different depths of cut. The workpieces were evaluated after grinding process by measuring the surface roughness Ra and confocal microscopy. For monitoring was used an accelerometer and vibration signal was collected by an oscilloscope. Digital signal processing techniques were performed, identifying a range of frequencies between 800 Hz and 2 kHz that best correlate with the condition of the machined ceramic. There was a correlation between the vibration and the integrity of the ceramics workpiece after grinding process. Moreover, the increase of the vibration is directly proportional to the surface roughness each cutting depth used. It follows that the vibration can be used to monitor the grinding of ceramics due to their relationship with the condition of the workpieces.
Keywords: Monitoring of Grinding Process; Advanced Ceramics; Vibration Signal; Spectral Analysis